2016
DOI: 10.2119/molmed.2016.00041
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK Signaling Regulates TGFβ-Induced Epithelial-Mesenchymal Transition of Lens Epithelial Cells through MRTF-A

Abstract: Transforming growth factor (TGF)-β-induced epithelial-mesenchymal transition (EMT) leads to the formation of ocular fibrotic pathologies, such as anterior subcapsular cataract and posterior capsule opacification. Remodeling of the actin cytoskeleton, mediated by the Rho family of GTPases, plays a key role in EMT. However, how actin dynamics affect downstream markers of EMT has not been fully determined. Our previous work suggests that myocardin-related transcription factor A (MRTF-A), an actin-binding protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 55 publications
1
65
1
1
Order By: Relevance
“…17 We proved that RhoA activation promoted MRTF-A translocation to the nucleus under strain status and SRF expression. Moreover, we showed that RhoA silence or ROCK inhibition prevented strain-induced expression of MRTF-A and SRF, which corresponded with the absence of a-SMA, suggesting that mechanical signals through RhoA/ROCK-MRTF-A/SRF induce a-SMA expression.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…17 We proved that RhoA activation promoted MRTF-A translocation to the nucleus under strain status and SRF expression. Moreover, we showed that RhoA silence or ROCK inhibition prevented strain-induced expression of MRTF-A and SRF, which corresponded with the absence of a-SMA, suggesting that mechanical signals through RhoA/ROCK-MRTF-A/SRF induce a-SMA expression.…”
Section: Discussionmentioning
confidence: 73%
“…[15][16][17] Of these, RhoA is known to have a key role in actin cytoskeleton reorganization, regulation of cell shape, adhesion, and migration and transformation of cellular phenotypes. 17,18 The Rho kinase (ROCK) family members, including ROCK1 and ROCK2, are important effectors of RhoA. Analysis of ROCK1 and ROCK2 distribution in a recent study revealed a dramatically higher expression of ROCK2 in the eye.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β rapidly activates Rho family guanosine triphophatases (GTPases) (29). TGF-β dependent activation of RhoA pathway induces the translocation of myocardin related transcription factor A (MRTF-A) to the nucleus to regulate a profibrotic response (30,31). TGF-β activates mitogen-activated protein kinases, including (extracellular signal-regulated kinases) ERKs, p38, and c-Jun N-terminal kinases (JNKs) through their upstream kinase activators such as transforming growth factor-β activated kinase-1 (TAK1) (29).…”
Section: Foxo Transcription Factorsmentioning
confidence: 99%
“…ROCKs are ubiquitously expressed, though ROCK1 is not expressed in the brain and muscle [11]. They mediate a wide array of cellular processes in cytoskeleton organization and assembly, energy metabolism, cell proliferation, and epithelial-to-mesenchymal transition [12,13]. ROCKs are activated in the kidneys and in cultured cells of diabetic models [14,15].…”
Section: Introductionmentioning
confidence: 99%